2024
DOI: 10.3390/ph17030340
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antioxidant Potentials and Quantitative Phenolic Compounds Profiles among the Flowers and Leaves from Various Chrysanthemum morifolium Cultivars

Tham Thi Mong Doan,
Gia Han Tran,
Toan Khac Nguyen
et al.

Abstract: Chrysanthemum morifolium is a valuable plant that contains a wide range of phytochemical compounds and exhibits various biological activities. Ethanol extracts from both the leaves and flowers of 17 different cultivars of C. morifolium were tested for antioxidant activities using the 2,2-diphenyl-1-picrylhydrazyl and 2,2′-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) assays and were quantitatively analyzed for 12 phenolic compounds using high-performance liquid chromatography with diode-array detection. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Furthermore, the antibacterial activity of various plants was evaluated by testing their varied solvent extractions against a range of harmful bacteria. It was found that flowers were particularly beneficial in their practical uses [ 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the antibacterial activity of various plants was evaluated by testing their varied solvent extractions against a range of harmful bacteria. It was found that flowers were particularly beneficial in their practical uses [ 31 34 ].…”
Section: Discussionmentioning
confidence: 99%